Preparation method of high-strength titanium alloy capable of inhibiting cracks and high-strength titanium alloy
Patent Information
- Application Number
- CN202411055434.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-02
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2044-08-02
AI Technical Summary
当能量激光能量输入太高,导致熔池内的液态金属发生飞溅,从而造成球化,或使金属粉末过熔,加大了残余应力和裂纹出现的可能性,同时更多的液态金属进入熔池,造成熔池的不稳定性增加,进而由于熔池温度高造成了熔体汽化气液界面会形成反作用力和高温熔体的飞溅影响了熔池的稳定造成熔池的断裂
(1)采用本发明的制备方法制得的钛合金内部无裂纹,晶粒细小;通过添加一定质量的石墨烯与Y2O3进行复合,由于石墨烯具有优异的导热性能,在选区激光熔化成型过程中热传导速度加快,为α相分解向β相转变的过程提供了更大的驱动力,同时使上一层的成型层发生二次成形,导致β相向α相的转变的次数也增多,使次生α´相明显增加,且α、α´相更加细小;同时Y2O3的添加使高强钛合金的组织得到细化,经退火处理后发生明显的再结晶,细化晶粒,可提高成形性能。
Smart Images

Figure CN118957337B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of additive manufacturing technology, specifically to a method for preparing a high-strength titanium alloy that can suppress cracks and the high-strength titanium alloy itself. Background Technology
[0002] Titanium and titanium alloys possess excellent comprehensive properties such as low density, high strength, good toughness, and good biocompatibility, making them widely used in industries such as automotive, defense, biomedicine, and aerospace. However, the traditional processing of these parts is complex, often involving numerous steps such as casting, machining, and welding, resulting in low economic efficiency. When a component with a complex geometry is required, part processing becomes even more challenging. With the development of metal additive manufacturing technology, both traditional and complex-designed parts can be manufactured in a single piece, eliminating the need for post-processing and reducing manufacturing time. Furthermore, additive manufacturing technology reduces material waste, lowers energy consumption, and provides optimal design for lean manufacturing.
[0003] Graphene is a novel material with a single-layer, two-dimensional honeycomb lattice structure of tightly packed carbon atoms linked by sp² hybridization. It possesses excellent properties such as low density, high specific strength, high thermal conductivity, and self-lubrication. Utilizing the high chemical reactivity of titanium, it readily reacts with graphene to obtain a strongly bonded in-situ reaction interface. This allows for the combination of graphene's lightweight, high strength, toughness, and large specific surface area with the high-temperature resistance and fatigue resistance of titanium alloys, potentially leading to the development of higher-performance graphene-reinforced titanium-based composite materials.
[0004] SLM (Selective Laser Melting) technology, as a new manufacturing concept, has been widely applied in various industries, such as medical, aerospace, and automotive prototyping. However, the range of titanium alloy grades currently available for SLM printing is relatively limited. Commonly used grades include pure titanium, TC4, and TA15, while many traditional titanium alloy grades have not yet been used in SLM manufacturing. During SLM forming, as laser energy is input, the original powder particles absorb the energy and melt. When the energy is insufficient, the powder does not absorb enough energy to melt the metal powder, resulting in too little liquid metal in the weld bead, leading to discontinuities in the weld bead. The strong capillary force and convection of the liquid metal cause significant spheroidization within the weld bead. When the laser energy input is too high, the liquid metal in the molten pool splashes, causing spheroidization or over-melting of the metal powder. This increases the likelihood of residual stress and cracks. Simultaneously, more liquid metal enters the molten pool, increasing its instability. Furthermore, the high temperature causes vaporization of the melt, creating a reaction force at the gas-liquid interface. The splashing of high-temperature melt also affects the stability of the molten pool, leading to fracture. Additionally, unmelted powder particles and pores in the SLM forming process become crack initiation points under residual stress, resulting in cracks; this is particularly severe in high-strength titanium alloys.
[0005] In summary, there is an urgent need to develop a method for preparing high-strength titanium alloys that can suppress cracks. High-strength titanium alloys formed using the SLM method not only have high mechanical strength but also do not produce cracks. Summary of the Invention
[0006] The purpose of this invention is to provide a method for preparing a high-strength titanium alloy that can suppress cracks. This method is simple and low-cost, and the high-strength titanium alloy obtained not only has high mechanical strength but also does not produce cracks.
[0007] The technical problem solved by this invention is achieved by the following technical solution.
[0008] This invention provides a method for preparing a high-strength titanium alloy capable of suppressing cracks, comprising the following steps: Step S1: Disperse Y2O3 powder in an aqueous solution containing a cationic surfactant to obtain a Y2O3 suspension coated with a cationic surfactant; disperse graphene oxide in an alkaline solution to obtain a graphene oxide suspension. Step S2: Add graphene oxide suspension dropwise to Y2O3 suspension coated with cationic surfactant, mix evenly by mechanical stirring, filter and dry to obtain graphene oxide-Y2O3 composite powder; Dry graphene oxide-Y2O3 composite powder was heat-treated in an atmosphere of inert gas and H2 to obtain reduced graphene-Y2O3 composite powder. Step S3: High-strength titanium alloy powder and reduced graphene-Y2O3 composite powder are ball-milled at low energy to obtain reduced graphene-Y2O3-high-strength titanium alloy composite powder. Step S4: The reduced graphene-Y2O3-high-strength titanium alloy composite powder obtained in step S3 is subjected to SLM printing to obtain a high-strength titanium alloy that can suppress cracks.
[0009] Furthermore, in step S1, the mass ratio of graphene oxide to Y2O3 is 1:(1-3), the molar ratio of the cationic surfactant to Y2O3 is (1.25-1.3):1, and the concentration of the graphene oxide suspension is 0.01-0.02 g / mL.
[0010] Furthermore, in step S1, the Y2O3 particle size is 40-60 nm.
[0011] Furthermore, in step S1, the alkaline solution is a mixed alkaline solution of NaOH and Na2CO3, and the molar ratio of NaOH to Na2CO3 is 1:(2-3), and the concentration of NaOH is 0.04-0.05 g / mL.
[0012] Furthermore, in step S2, the volume ratio of the graphene oxide suspension to the Y2O3 suspension coated with the surfactant is (18-20):1.
[0013] Furthermore, in step S3, the mass percentage of the reduced graphene-Y2O3 composite powder is 0.1-0.5%.
[0014] Furthermore, in step S2, the specific process for obtaining the reduced graphene-Y2O3 composite powder is as follows: at a temperature of 850-920℃ and a pressure of 0.1-0.6 MPa, the dried graphene oxide-Y2O3 composite powder is heat-treated in an atmosphere of inert gas and H2 for 3-6 hours to obtain the reduced graphene-Y2O3 composite powder, wherein the volume ratio of inert gas to H2 is 100:(1-5).
[0015] Furthermore, in step S4, the laser volume energy density is 45-120 J / mm². 3 The 3D printing parameters used are as follows: laser power of 180-260W; laser scanning speed of 700-1300mm / s; scanning spacing of 0.08-0.12mm; and interlayer thickness of 0.03-0.06mm.
[0016] Furthermore, the method is characterized by including: Step S5: the high-strength titanium alloy obtained in step S4 is subjected to heat treatment. In a vacuum environment, the temperature is first raised to 500-600℃ and held for 0.5-1h, then the temperature is raised to 800℃-850℃ and held for 2-4h. Argon gas is introduced to 2-4 bar and the alloy is rapidly cooled to room temperature before being taken out. The cooling rate is 45-80℃ / min.
[0017] Another aspect of the present invention provides a high-strength titanium alloy, which is prepared by the above-described preparation method.
[0018] The beneficial effects of the method for preparing high-strength titanium alloys capable of suppressing cracks according to embodiments of the present invention include: (1) The titanium alloy prepared by the method of the present invention has no internal cracks and has fine grains. By adding a certain amount of graphene and Y2O3 to form a composite, the heat conduction speed is accelerated during the selective laser melting process due to the excellent thermal conductivity of graphene, which provides a greater driving force for the transformation of α phase to β phase. At the same time, the upper forming layer undergoes secondary forming, which leads to an increase in the number of transformations of β phase to α phase, resulting in a significant increase in secondary α' phase and finer α and α' phases. Meanwhile, the addition of Y2O3 refines the microstructure of the high-strength titanium alloy. After annealing, significant recrystallization occurs, refining the grains and improving the forming performance.
[0019] (2) The two-dimensional lattice mismatch degree δ=6.54% between the (111) crystal plane of Y2O3 and the (110) crystal plane of TiC indicates that Y2O3 can serve as an effective heterogeneous nucleation core for TiC to refine the grains. Simultaneously, the addition of graphene, under the action of a high-energy laser beam, resulted in an in-situ reaction between graphene and the titanium alloy: Ti+C→TiC, producing a large number of TiC nanoparticles and undecomposed graphene. During the forming process, Y2O3 better forms a composite phase structure with TiC, and the increased number of nucleation cores makes the grains finer. The presence of nano-TiC particles also facilitates the formation of deformation twins, which promotes the orderly arrangement of atoms in the nanocomposite material during deformation. This suppresses dislocation movement due to severe lattice distortion and deformation twinning at interfaces formed by different orientations, thereby reducing crack formation.
[0020] (3) Through the composite addition of graphene and Y2O3 in this invention, finer α, α´, and β phases are generated during the printing solidification process. Simultaneously, the in-situ generated TiC nanoparticles and unreacted graphene agglomerate inhibit the growth of titanium-based composite grains, resulting in grain refinement. The addition of an appropriate amount of Y2O3 increases the undercooling of the molten pool, increasing the system nucleation rate, thereby refining the grains. Unmelted Y2O3 can act as a heterogeneous nucleation core, improving the nucleation rate and refining the grains. The TiC nanoparticles, being dispersed and uniformly distributed, provide dispersion strengthening. According to the Hall-Patch mechanism, generally, the smaller the grain size, the higher its yield strength.
[0021] (4) By observing the microstructure of the printed melt under different process parameters, it was found that adding a certain amount of graphene and Y2O3 can reduce cracks and porosity in high-strength titanium alloys and refine the grains. The effect was best when the mass fraction of graphene and Y2O3 composite powder accounted for 0.3% of the total printed powder. The density of the melt was 99.3%, the room temperature tensile strength was as high as 1630 MPa, the yield strength was as high as 1504 MPa, the elongation was as high as 9.6%, and the hardness was as high as 348 HV. In addition, the titanium alloy composite material prepared by this invention has excellent high-temperature tensile properties, with an elongation of up to 17% and a tensile strength of up to 1156 MPa at 500℃. Attached Figure Description
[0022] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the embodiments will be briefly introduced below. It should be understood that the following drawings only show some embodiments of the present invention and should not be regarded as a limitation on the scope. For those skilled in the art, other related drawings can be obtained based on these drawings without creative effort.
[0023] Figure 1 Metallographic image of the high-strength titanium alloy obtained in Example 1 of this invention; Figure 2 Metallographic image of the high-strength titanium alloy obtained in Example 2 of this invention; Figure 3 Metallographic image of the high-strength titanium alloy obtained in Example 3 of this invention; Figure 4 This is a metallographic image of the high-strength titanium alloy prepared in Comparative Example 1 of the present invention. Detailed Implementation
[0024] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall be followed. Where the manufacturers of reagents or instruments are not specified, they are all conventional products that can be purchased commercially.
[0025] This invention provides a method for preparing a high-strength titanium alloy that can suppress cracking, comprising the following steps: Step S1: Disperse Y2O3 powder in an aqueous solution containing a cationic surfactant to obtain a Y2O3 suspension coated with a cationic surfactant; disperse graphene oxide in an alkaline solution to obtain a graphene oxide suspension. Step S2: Add graphene oxide suspension dropwise to Y2O3 suspension coated with cationic surfactant, mix evenly by mechanical stirring, filter and dry to obtain graphene oxide-Y2O3 composite powder; Dry graphene oxide-Y2O3 composite powder was heat-treated in an atmosphere of inert gas and H2 to obtain reduced graphene-Y2O3 composite powder. Step S3: High-strength titanium alloy powder and reduced graphene-Y2O3 composite powder are ball-milled at low energy to obtain reduced graphene-Y2O3-high-strength titanium alloy composite powder. Step S4: The reduced graphene-Y2O3-high-strength titanium alloy composite powder obtained in step S3 is subjected to SLM printing to obtain a high-strength titanium alloy that can suppress cracks.
[0026] It should be noted that the high-strength titanium alloy mentioned in this invention refers to a titanium alloy with a tensile strength between 1100 and 1400 MPa at room temperature, which is composed of near-β titanium alloy and metastable β titanium alloy.
[0027] It should be noted that dispersing Y2O3 powder in an aqueous solution containing a cationic surfactant to obtain a Y2O3 suspension coated with a cationic surfactant; and dispersing graphene oxide in an alkaline solution to obtain a graphene oxide suspension; can all be dispersed by ultrasonication or other dispersion methods. The embodiments in this invention are illustrated by ultrasonic dispersion.
[0028] The cationic surfactants described herein include nitrogen-containing organic amine derivatives. Because the nitrogen atoms in their molecules contain lone pairs of electrons, they can bind with hydrogen atoms in acid molecules via hydrogen bonds, causing the amino group to acquire a positive charge. Preferred cationic surfactants include hexadecyltrimethylammonium bromide, octadecyldimethylbenzylammonium chloride, and hexadecylpyridinium chloride.
[0029] The titanium alloy prepared by the method of this invention has no internal cracks and has fine grains. By adding a certain amount of graphene and Y2O3 to form a composite, the excellent thermal conductivity of graphene accelerates the heat conduction speed during selective laser melting, providing a greater driving force for the transformation of α phase to β phase. At the same time, it causes secondary forming of the upper forming layer, resulting in an increase in the number of transformations from β phase to α phase, which significantly increases the number of secondary α' phases, and the α and α' phases are finer. Meanwhile, the addition of Y2O3 refines the microstructure of the high-strength titanium alloy. After annealing, significant recrystallization occurs, refining the grains and improving the forming performance.
[0030] The two-dimensional lattice mismatch degree δ=6.54% between the (111) crystal plane of Y2O3 and the (110) crystal plane of TiC indicates that Y2O3 can serve as an effective heterogeneous nucleation core for TiC to refine the grains. Simultaneously, the addition of graphene, under the action of a high-energy laser beam, resulted in an in-situ reaction between graphene and the titanium alloy: Ti + C → TiC, producing a large number of TiC nanoparticles and undecomposed graphene. During the forming process, Y2O3 better forms a composite phase structure with TiC, and the increased number of nucleation cores leads to finer grains. The presence of nano-TiC particles also facilitates the formation of deformation twins, which promotes the orderly arrangement of atoms in the nanocomposite material during deformation. This suppresses dislocation movement due to severe lattice distortion and deformation twinning at interfaces formed by different orientations, thereby reducing crack formation.
[0031] By combining graphene and Y₂O₃ in this invention, finer α, α', and β phases are generated during the printing solidification process. Simultaneously, the in-situ generated TiC nanoparticles and unreacted graphene agglomerate inhibit the growth of titanium-based composite grains, resulting in grain refinement. The addition of an appropriate amount of Y₂O₃ increases the undercooling of the molten pool, increasing the system nucleation rate and thus refining the grains. Unmelted Y₂O₃ can act as heterogeneous nucleation nuclei, improving the nucleation rate and refining the grains. The TiC nanoparticles, being dispersed and uniformly distributed, provide dispersion strengthening. According to the Hall-Patch mechanism, generally, smaller grain sizes result in higher yield strength.
[0032] By observing the microstructure of the printed melt under different process parameters, it was found that adding a certain amount of graphene and Y2O3 can reduce cracks and porosity in high-strength titanium alloys and refine the grains. The effect was optimal when the mass fraction of the graphene and Y2O3 composite powder was 0.3%. The melt density was 99.3%, the room temperature tensile strength reached 1630 MPa, the yield strength reached 1501 MPa, the elongation reached 9.6%, and the hardness reached 342 HV. In addition, the titanium alloy composite material prepared by this invention has excellent high-temperature tensile properties, with an elongation of up to 17% and a tensile strength of up to 1156 MPa at 500℃.
[0033] Specifically, in step S1, the mass ratio of graphene oxide to Y2O3 is 1:(1-3), the molar ratio of the cationic surfactant to Y2O3 is (1.25-1.3):1, and the concentration of the graphene suspension is 0.01-0.02 g / mL.
[0034] By limiting the ratio of graphene oxide and Y2O3, it is beneficial to ensure thorough mixing of the cationic Y2O3 with the negatively charged graphene suspension, and to avoid the aggregation of both.
[0035] Specifically, in step S1, the Y2O3 particle size is 40-60 nm.
[0036] If the Y2O3 particles are too large, they will not be able to refine the material during the printing process and may even become a source of cracks, leading to printing failure or material failure.
[0037] Specifically, in step S1, the alkaline solution is a mixed alkaline solution of NaOH and Na2CO3, and the molar ratio of NaOH to Na2CO3 is 1:(2-3), and the concentration of NaOH is 0.04-0.05 g / mL.
[0038] Specifically, in step S2, the volume ratio of the graphene oxide suspension to the Y2O3 powder suspension coated with the surfactant is (18-20):1.
[0039] Specifically, in step S3, the mass percentage of reduced graphene-Y2O3 composite powder is 0.1-0.5%.
[0040] Specifically, in step S2, the process of obtaining the reduced graphene-Y2O3 composite powder is as follows: at a temperature of 850-920℃ and a pressure of 0.1-0.6 MPa, the dried graphene oxide-Y2O3 composite powder is heat-treated in an atmosphere of inert gas and H2 for 3-6 hours to obtain the reduced graphene-Y2O3 composite powder, wherein the volume ratio of inert gas to H2 is 100:(1-5).
[0041] Preferably, the high-strength titanium alloy powder has a particle size of 15-53 μm.
[0042] Specifically, in step S3, the ball speed of the low-energy ball ink is 60-300 r / min, the ball-to-material ratio is 5:1, and the ball milling time is 3-24 h.
[0043] Specifically, in step S4, the laser volume energy density is 45-120 J / mm². 3 The 3D printing parameters used are as follows: laser power of 180-260W; laser scanning speed of 700-1300mm / s; scanning spacing of 0.08-0.12mm; and interlayer thickness of 0.03-0.06mm.
[0044] Specifically, it also includes: Step S5: The high-strength titanium alloy obtained in step S4 is heat-treated. In a vacuum environment, the temperature is first raised to 500-600℃ and held for 0.5-1h, then the temperature is raised to 800℃-850℃ and held for 2-4h. Argon gas is introduced to 2-4 bar and the alloy is rapidly cooled to room temperature before being taken out. The cooling rate is 45-80℃ / min.
[0045] When the cooling rate is lower than 45℃ / min, some of the corresponding specimens will break abnormally or have an elongation as low as 2-4% when performing tensile tests.
[0046] In another aspect, the present invention proposes a high-strength titanium alloy that can suppress cracks, wherein the high-strength titanium alloy is prepared by the above preparation method.
[0047] To further illustrate the present invention, the following detailed description of a method for reusing non-finished aluminum alloy powder provided by the present invention is provided in conjunction with embodiments, but these descriptions should not be construed as limiting the scope of protection of the present invention.
[0048] The high-strength titanium alloy used in the following embodiments is represented by Ti-55531 titanium alloy, but it should not be construed as a limitation on the scope of protection of this invention.
[0049] Example 1
[0050] This embodiment provides a method for preparing a high-strength titanium alloy capable of suppressing cracks, which includes the following steps: Step S1: Weigh 36.4g of hexadecyltrimethylammonium bromide and dissolve it in 50ml of aqueous solution to obtain hexadecyltrimethylammonium bromide aqueous solution. Use ultrasonic dispersion to disperse 18g of Y2O3 powder with a particle size of 40-60nm in 50ml of hexadecyltrimethylammonium bromide aqueous solution to obtain a Y2O3 powder suspension coated with cationic surfactant. Weigh out 40g of NaOH and 212g of Na2CO3 and dissolve them in 1000ml of water to obtain a mixed alkaline solution. Use ultrasonic dispersion to disperse 6g of graphene oxide in 1000mL of the mixed alkaline solution at room temperature to obtain a graphene oxide suspension. Step S2: Add 1000ml of graphene oxide suspension to 50ml of Y2O3 suspension coated with cationic surfactant, mix evenly by mechanical stirring, filter and dry to obtain graphene oxide-Y2O3 composite powder. At a temperature of 850℃ and a pressure of 0.1 MPa, the dried graphene oxide-Y2O3 composite powder was heat-treated in an atmosphere of inert gas and H2 for 3 hours to obtain reduced graphene-Y2O3 composite powder. Step S3: Weigh 1990g of Ti-55531 titanium alloy powder with a particle size of 15-53μm and 10g of reduced graphene-Y2O3 composite powder obtained in step S2. Perform low-energy ball milling on the weighed Ti-55531 titanium alloy powder and the reduced graphene-Y2O3 composite powder. The ball milling speed is 60r / min, the ball-to-material ratio is 5:1, and the ball milling time is 3h. Reduced graphene-Y2O3-high-strength titanium alloy composite powder is obtained. Step S4: The reduced graphene-Y2O3-high-strength titanium alloy composite powder obtained in step S3 is subjected to SLM printing to obtain a high-strength titanium alloy that can suppress cracks; the laser energy density is 45J / mm3; the 3D printing parameters used are: laser power of 180W; laser scanning speed of 700mm / s; scanning spacing of 0.08mm; interlayer thickness of 0.03mm; The high-strength titanium alloy obtained in step S4 was heat-treated in a vacuum environment. First, the temperature was raised to 500℃ and held for 0.5h, then the temperature was raised to 800℃ and held for 2h. Argon gas was introduced to 2 bar and the alloy was rapidly cooled to room temperature before being removed. The cooling rate was 45℃ / min.
[0051] The performance indicators of the finally obtained high-strength titanium alloy are shown in Table 1, and the metallographic structure of the obtained high-strength titanium alloy is as follows: Figure 1 As shown.
[0052] Example 2
[0053] This embodiment provides a method for preparing a high-strength titanium alloy capable of suppressing cracks, which includes the following steps: Step S1: Weigh 42.5g of octadecyl dimethyl benzyl ammonium chloride and dissolve it in 50ml of aqueous solution to obtain an octadecyl dimethyl benzyl ammonium chloride aqueous solution. Disperse 18g of Y2O3 powder with a particle size of 40-60nm in 50ml of octadecyl dimethyl benzyl ammonium chloride aqueous solution by ultrasonic dispersion to obtain a Y2O3 powder suspension coated with cationic surfactant. Weigh out 40g of NaOH and 318g of Na2CO3 and dissolve them in 800ml of water to obtain a mixed alkaline solution. Use ultrasonic dispersion to disperse 9g of graphene oxide in 800mL of the mixed alkaline solution at room temperature to obtain a graphene oxide suspension. Step S2: Add 800ml of graphene oxide suspension to 50ml of Y2O3 suspension coated with cationic surfactant, mix evenly by mechanical stirring, filter and dry to obtain graphene oxide-Y2O3 composite powder. At a temperature of 920℃ and a pressure of 0.6 MPa, the dried graphene oxide-Y2O3 composite powder was heat-treated in an atmosphere of inert gas and H2 for 6 hours to obtain reduced graphene-Y2O3 composite powder. Step S3: Weigh 1994g of Ti-55531 titanium alloy powder with a particle size of 15-53μm and 6g of reduced graphene-Y2O3 composite powder obtained in step S2. Perform low-energy ball milling on the weighed Ti-55531 titanium alloy powder and reduced graphene-Y2O3 composite powder at a ball milling speed of 300r / min, a ball-to-material ratio of 5:1, and a ball milling time of 24h to obtain reduced graphene-Y2O3-high-strength titanium alloy composite powder. Step S4: The reduced graphene-Y2O3-high-strength titanium alloy composite powder obtained in step S3 is subjected to SLM printing to obtain a high-strength titanium alloy that can suppress cracks; the laser energy density is 120J / mm3; the 3D printing parameters used are: laser power of 260W; laser scanning speed of 1300mm / s; scanning spacing of 0.12mm; interlayer thickness of 0.06mm; The high-strength titanium alloy obtained in step S4 was heat-treated in a vacuum environment. First, the temperature was raised to 600℃ and held for 1 hour, then the temperature was raised to 850℃ and held for 4 hours. Argon gas was introduced to 4 bar and the alloy was rapidly cooled to room temperature before being taken out. The cooling rate was 80℃ / min.
[0054] The performance indicators of the finally obtained high-strength titanium alloy are shown in Table 1, and the metallographic structure of the obtained high-strength titanium alloy is as follows: Figure 2 As shown.
[0055] Example 3
[0056] This embodiment provides a method for preparing a high-strength titanium alloy capable of suppressing cracks, which includes the following steps: Step S1: Weigh 34g of hexadecylpyridinium chloride and dissolve it in 50ml of aqueous solution to obtain hexadecylpyridinium chloride aqueous solution. Use ultrasonic dispersion to disperse 18g of Y2O3 powder with a particle size of 40-60nm in 50ml of hexadecylpyridinium chloride aqueous solution to obtain a Y2O3 powder suspension coated with cationic surfactant. Weigh out 40g of NaOH and 212g of Na2CO3 and dissolve them in 900ml of water to obtain a mixed alkaline solution. Use ultrasonic dispersion to disperse 18g of graphene oxide in 900mL of the mixed alkaline solution at room temperature to obtain a graphene oxide suspension. Step S2: Add 900ml of graphene oxide suspension to 50ml of Y2O3 suspension coated with cationic surfactant, mix evenly by mechanical stirring, filter and dry to obtain graphene oxide-Y2O3 composite powder. At a temperature of 885℃ and a pressure of 0.3 MPa, the dried graphene oxide-Y2O3 composite powder was heat-treated in an atmosphere of inert gas and H2 for 4.5 h to obtain reduced graphene-Y2O3 composite powder. Step S3: Weigh 1992g of Ti-55531 titanium alloy powder with a particle size of 15-53μm and 8g of reduced graphene-Y2O3 composite powder obtained in step S2. Perform low-energy ball milling on the weighed Ti-55531 titanium alloy powder and the reduced graphene-Y2O3 composite powder. The ball milling speed is 180r / min, the ball-to-material ratio is 5:1, and the ball milling time is 14h. Reduced graphene-Y2O3-high-strength titanium alloy composite powder is obtained. Step S4: The reduced graphene-Y2O3-high-strength titanium alloy composite powder obtained in step S3 is subjected to SLM printing to obtain a high-strength titanium alloy that can suppress cracks; the laser energy density is 80J / mm3; the 3D printing parameters used are: laser power of 220W; laser scanning speed of 1000mm / s; scanning spacing of 0.1mm; interlayer thickness of 0.45mm; The high-strength titanium alloy obtained in step S4 was heat-treated in a vacuum environment. First, the temperature was raised to 550℃ and held for 0.8h, then the temperature was raised to 825℃ and held for 3h. Argon gas was introduced to 3 bar and the alloy was rapidly cooled to room temperature before being removed. The cooling rate was 60℃ / min.
[0057] The performance indicators of the finally obtained high-strength titanium alloy are shown in Table 1, and the metallographic structure of the obtained high-strength titanium alloy is as follows: Figure 3 As shown.
[0058] Comparative Example 1 (compared to Example 2, the mass ratio of reduced graphene-Y2O3 composite powder in step S3 is too high) Compared with Example 2, the difference is that in step S3, 1980g of Ti-55531 titanium alloy powder with a particle size of 15-53μm is weighed, and 20g of reduced graphene-Y2O3 composite powder obtained in step S2 is weighed.
[0059] The performance indicators of the finally obtained high-strength titanium alloy are shown in Table 1, and the metallographic structure of the obtained high-strength titanium alloy is as follows: Figure 4 As shown.
[0060] Comparative Example 2 (compared to Example 2, the mass percentage of reduced graphene-Y2O3 composite powder in step S3 is too low) Compared with Example 2, the difference is that in step S3, 1998g of Ti-55531 titanium alloy powder with a particle size of 15-53μm was weighed, and 2g of reduced graphene-Y2O3 composite powder obtained in step S2 was weighed.
[0061] The performance indicators of the final high-strength titanium alloy are shown in Table 1.
[0062] Comparative Example 3 (different heat treatment regime in step S5 compared to Example 2 - slower cooling rate) Compared with Example 2, the difference is that in step S5, the obtained high-strength titanium alloy is heat-treated by heating to 550°C in a vacuum environment and holding for 3 hours. After cooling to room temperature in the furnace, it is taken out at a cooling rate of 10°C / min.
[0063] Comparative Example 4 (different heat treatment regime in step S5 compared to Example 2 - faster cooling rate) The difference from Example 2 is that in step S5, the cooling rate is 120°C / min.
[0064] Comparative Example 5 (Graphene was dispersed in water in step S1 compared to Example 2) Compared with Example 2, the difference is that in step S1, 6g of graphene oxide is dispersed in 1000mL of aqueous solution at room temperature using ultrasonic dispersion to obtain a graphene oxide suspension.
[0065] The performance indicators of the final high-strength titanium alloy are shown in Table 1.
[0066] Table 1 compares the performance indicators of the titanium alloys obtained in Examples 1-3 and Comparative Examples 1-3: Table 1
[0067] The high-strength titanium alloys prepared in Examples 1-3 are as follows: Figure 1-3As shown, the high-strength titanium alloy has no cracks or voids and has good mechanical properties. The density of the melt measured in the experiment can reach 99.3%, and as shown in Table 1, the obtained high-strength titanium alloy has no cracks and has high density, tensile strength, yield strength, elongation and hardness.
[0068] By comparing Comparative Examples 1-2 with Examples 1-3, it can be seen that as the graphene-Y2O3 content gradually increases, no cracks are generated inside the melt, and the number of pores first decreases and then increases. When the graphene-Y2O3 content is low, the ideal gain effect cannot be achieved, but it can still effectively improve the crack situation in the melt. As the graphene-Y2O3 content increases to a certain proportion, the heat conduction speed during the forming process is accelerated, and an in-situ reaction occurs on the titanium alloy, producing a large number of TiC nanoparticles. At the same time, Y2O3 can also combine with the generated TiC to form a composite structure, increasing the nucleation core, refining the grains, and the increase in grain boundaries can suppress dislocation movement and reduce crack generation. As its content continues to increase, graphene cannot decompose during the forming process and will inevitably agglomerate, resulting in coarser TiC particles, leading to the degradation of the pinning effect. At the same time, a large amount of graphene-Y2O3 composite powder does not melt during the printing process, and pores and cracks are easily formed around these unmelted particles during the printing process.
[0069] Comparing Comparative Examples 3-4 with Example 2, the heat treatment temperature was lower, failing to reach the corresponding phase transformation temperatures. Only internal stress was eliminated, and the internal microstructure of the material remained unchanged, equivalent to the printed state in additive manufacturing. After heat treatment, the β phase precipitated in the microstructure. Different phases affect the deformation mechanism of the material, thus improving the plasticity of the alloy to some extent. When the cooling rate was lower than that of this application, the tensile strength and yield strength decreased slightly, but the elongation decreased significantly, reaching only 2%. When the cooling rate was higher than that of this application, the tensile strength decreased by nearly 100 MPa, but the elongation remained low.
[0070] Compared with Example 2, in Comparative Example 5, the graphene did not adsorb negative ions and could not be mixed evenly with the Y2O3 coated by the anodic activator, resulting in graphene agglomeration. This led to more cracks in the printed high-strength titanium alloy and poor mechanical properties.
[0071] The above description of the disclosed embodiments enables those skilled in the art to make or use the invention. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the invention. Therefore, the invention is not to be limited to the embodiments shown herein, but is to be accorded the widest scope consistent with the principles and novel features disclosed herein.
[0072] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A method for preparing a high-strength titanium alloy capable of suppressing cracks, characterized in that, Includes the following steps: Step S1: Disperse Y2O3 powder in an aqueous solution containing a cationic surfactant to obtain a Y2O3 suspension coated with a cationic surfactant; disperse graphene oxide in an alkaline solution to obtain a graphene oxide suspension. Step S2: Add graphene oxide suspension dropwise to Y2O3 suspension coated with cationic surfactant, mix evenly by mechanical stirring, filter and dry to obtain graphene oxide-Y2O3 composite powder; Dry graphene oxide-Y2O3 composite powder was heat-treated in an atmosphere of inert gas and H2 to obtain reduced graphene-Y2O3 composite powder. Step S3: High-strength titanium alloy powder and reduced graphene-Y2O3 composite powder are ball-milled at low energy to obtain reduced graphene-Y2O3-high-strength titanium alloy composite powder. Step S4: The reduced graphene-Y2O3-high-strength titanium alloy composite powder obtained in step S3 is subjected to SLM printing to obtain a high-strength titanium alloy that can suppress cracks.
2. The preparation method according to claim 1, characterized in that, In step S1, the mass ratio of graphene oxide to Y2O3 is 1:(1-3), the molar ratio of the cationic surfactant to Y2O3 is (1.25-1.3):1, and the concentration of the graphene oxide suspension is 0.01-0.02 g / mL.
3. The preparation method according to claim 1, characterized in that, In step S1, the Y2O3 particle size is 40-60 nm.
4. The preparation method according to claim 3, characterized in that, In step S1, the alkaline solution is a mixed alkaline solution of NaOH and Na2CO3, and the molar ratio of NaOH to Na2CO3 is 1:(2-3), and the concentration of NaOH is 0.04-0.05 g / mL.
5. The preparation method according to claim 1, characterized in that, In step S2, the volume ratio of the graphene oxide suspension to the Y2O3 suspension coated with the surfactant is (18-20):
1.
6. The preparation method according to claim 1, characterized in that, In step S3, the mass percentage of reduced graphene-Y2O3 composite powder is 0.1-0.5%.
7. The preparation method according to claim 1, characterized in that, In step S2, the specific process for obtaining the reduced graphene-Y2O3 composite powder is as follows: at a temperature of 850-920℃ and a pressure of 0.1-0.6 MPa, the dried graphene oxide-Y2O3 composite powder is heat-treated in an atmosphere of inert gas and H2 for 3-6 hours to obtain the reduced graphene-Y2O3 composite powder, wherein the volume ratio of inert gas to H2 is 100:(1-5).
8. The preparation method according to claim 1, characterized in that, In step S4, the laser volume energy density is 45-120 J / mm². 3 The 3D printing parameters used are as follows: laser power of 180-260W; laser scanning speed of 700-1300mm / s; scanning spacing of 0.08-0.12mm; and interlayer thickness of 0.03-0.06mm.
9. The preparation method according to claim 1, characterized in that, Also includes: Step S5: The high-strength titanium alloy obtained in step S4 is subjected to heat treatment. In a vacuum environment, the temperature is first raised to 500-600℃ and held for 0.5-1h, then the temperature is raised to 800℃-850℃ and held for 2-4h. Argon gas is introduced to 2-4 bar and the alloy is rapidly cooled to room temperature. The cooling rate is 45-80℃ / min.
10. A high-strength titanium alloy capable of suppressing cracks, characterized in that, It is prepared by the preparation method according to any one of claims 1-9.
Citation Information
Patent Citations
Titanium alloy surface multi-element laser alloyed layer and preparation method thereof
CN103966598A
Nanoparticle dispersion strengthened titanium powder with improved uniformity and manufacturing method thereof
KR102370831B1